The Influence of College Students’ Innovation and Entrepreneurship Intention in the Art Field of Art Film and Television Appreciation by Deep Learning Under Entrepreneurial Psychology - Wang, Minxin; Shao, Yefan; Fu, Shiman; Ye, Lele; Li, Hongming; Yang, Guodong (Frontiers in Psychology, 2022)
There are many films and televisions (FAT) on the Internet, but the quality is uneven. This study explores the ability of college students to screen good films and resist bad films in television works in such a large environment. In the deep learning model of FAT, the ability of college students to think about the ideas expressed and the degree of influence on college students’ values are analyzed. Based on this conceptual basis, a questionnaire is designed for the intention and influencing factors of college students’ FAT innovation and entrepreneurship. It reflects the influence of concentration on FAT learning, the cognitive level of deep learning, the ability to process deep learning ideas, the feeling of the teaching process, and the process of self-learning, which all positively impact college students’ FAT entrepreneurial intentions. The importance of innovative deep learning is highlighted, which proves that a good deep learning course guidance method can improve students’ interest and ability and provide a reference for relevant colleges and universities to cultivate pertinent talents of the field of FAT.